Frequency and Persistence of Fecal Shedding Following Exposure of Laying Hens to Different Oral Doses of Salmonella enteritidis - Gast, Richard K.; Guraya, Rupa; Holt, Peter S. (International Journal of Poultry Science, 2011)
Infection of egg-laying poultry with Salmonella enteritidis and the associated transmission of illness to consumers of contaminated eggs has been a prominent international public health concern for many years. Testing and risk reduction programs for laying flocks have been implemented in many nations with some success. However, several critical parameters of S. enteritidis infections in chickens, including the relationship between the magnitude of oral exposure and the frequency and duration of bacterial shedding in voided feces, remain incompletely defined or explained. In the present study, groups of laying hens were experimentally infected with oral doses of 104, 106, or 108 CFU of a phage type 13a strain of S. enteritidis and the frequency at which the pathogen was shed in voided feces was determined at 8 weekly post-inoculation intervals. At 1 wk post-inoculation, the frequency of fecal shedding of S. enteritidis ranged from 23.8% for the 104 CFU dose to 87.5% for the 108 CFU dose. No fecal shedding was detected after 3 wk post-inoculation from hens inoculated with 104 CFU, but a small proportion (2.5% to 5.0%) of hens that received doses of 106 or more CFU of S. enteritidis were still shedding at 8 wk post-inoculation. The results of this study indicate that the oral exposure dose can significantly influence the frequency and duration of S. enteritidis fecal shedding into the environment by infected laying hens. A more complete understanding of how different levels of exposure are detected by particular sampling methods will support the effective application and interpretation of testing protocols for controlling poultry infections and preventing transmission to humans.